Existence of Positive Solutions for Multiterm Fractional Differential Equations of Finite Delay with Polynomial Coefficients - A. Babakhani; E. Enteghami (Abstract and Applied Analysis)
Existence of positive solutions has been studied by A. Babakhani and V. Daftardar-Gejji (2003) in case of multiterm nonautonomous fractional differential equations with constant coefficients. In the present paper we discuss existence of positive solutions in case of multiterm fractional differential equations of finite delay with polynomial coefficients.